Kampanye Hitam Pilgub DKI 2017: Analisis Wacana van Dijk pada Meme di Media Sosial - Saleh, Gunawan (Faculty of Communications Science, Dr. Soetomo University, 2018)
The rise of black campaign can be felt directly even outside of Jakarta. Shapes of black campaign were varied as such leaflets and memes. If seen the use of social media becomes an alternative as major media. As taken from the website www.brilio.net serving many of Jakarta Election-related memes. This study is a qualitative observation with data collection non-participant. Analysis of the data was measured by using Elements of by van Dijk, then researcher take full conclusion. In the Agus-Sylvi message want to publicly disseminated is Susilo Bambang Yudhoyono (SBY) figure of Hypocrisy and only waffle only and is not consistent with the his statement. Then Ahok figure who abused campaign attribute in the form of banners. the government seemed siding and breaking the rules. Anies-Sandi message to black campaign in circulation is Anies figure coward, running away from debate. It is also inconsistent. Nuanced political message black campaign is circulating in cyberspace through social media. The government should regulate it, because it will have a negative impact on the democratic party.